Engagement in Open Source Software projects via Summer of Code programs - Silva, Jefferson de Oliveira (2019)
Several Open Source Software (OSS) projects need a constant influx of newcomers, as member disengagement poses sustainability challenges. A significant hurdle for OSS projects is to discover ways to attract and retain newcomers. Some OSS projects expect to onboard newcomers and receive contributions by participating in Summer of Code programs. Such programs aim at fostering software development by typically matching OSS projects with students. Nevertheless, despite their growing popularity, there is little information about what makes students engage in OSS by participating in such programs and how it can benefit OSS projects. Summer of Code programs are typically laborious and time-consuming, and several OSS projects do not have enough empirical evidence to make a well-informed decision about the actual costs of participating in such programs, which could hinder the projects\' capacity to address their needs timely. In this thesis, our goal is to reveal the students\' engagement in OSS projects via Summer of Code programs. We focused on Google Summer of Code as our case study, as it is best-known, with several developers from across the globe, and in operation for more than a decade. We employed multiple empirical methods such as interviews, surveys, and quantitative analysis of data mined from source code repositories. We claim two main novel contributions: the empirical identification of the tasks that OSS projects accomplish to motivate students in such programs, and; the empirical identification of factors that influence students to engage in OSS via Summer of Code programs. With our results, OSS projects have a concise and structured description of what makes students engage in OSS projects when they participate in such programs; new students can benefit from former students\' experiences, and; researchers have a theoretical foundation to devise methods and models. In this way, we believe that OSS projects can ultimately gain more contributions from students interested in short and long-term collaboration.